Diversity and Conservation of Philippine Land Vertebrates: An Annotated Bibliography - Balete, Danilo S.; Miranda Jr., Hector C.; Heaney, Lawrence R.; Rieger, James F. (Silliman Journal, 2024)
Summaries of 111 important publications on the diversity and conservation of Philippine land vertebrates are presented as an aid to research and management.